Sub-THz nonresonant detection in AlGaN/GaN heterojunction FETs - Golenkov, A.G.; Zhuravlev, K.S.; Gumenjuk-Sichevska, J.V.; Lysiuk, I.O.; Sizov, F.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Un-cooled AlGaN/GaN-based heterojunction field-effect transistors (HFET) designed on sapphire (0001) substrates were considered as 140 GHz direct detection detectors without any specially attached antennas. The noise equivalent power (NEP) of these detectors was ~ 10⁻¹⁰ W/Hz¹/² in the observed radiation frequency range at ambient temperatures. It has been shown that the ultimate value for the AlGaN/GaN HFET detectors (in 0.25-μm technology) can reach NEPopt ≈ 6•10⁻¹² W/Hz¹/² , and it is 3-fold lower than that for Si MOSFET (in 0.35-μm technology).